the EFFECT OF PURPLE SWEET POTATO (Ipomea Batatas L. Poir) ON INCREASING HBW IN PREGNANT WOMEN AT ROMAULI CLINIC - Muthia Sari Mardha; Endriyani Syafitri; Maya Lestari (Jurnal Ilmu Kebidanan, 2023)
The number of anemia in pregnant women in Indonesia based on Riskesdas data has increased compared to 2013, in 2013 there were 37.1% of pregnant women with anemia while in 2018 it increased to 48.9%. This study aims to determine the effect of purple sweet potato stew on increasing Hb in pregnant women. This study used a one group pretest and posttest research design. The population in this study were all pregnant women who came to visit the clinic during April, samples were taken by accidental sampling. The analysis in this study used the Wilcoxon test. The results of this study showed that the results of the normality test were 0.000 <0.05, this means that the data was not normally distributed, and the Wilcoxon test was carried out to obtain p = 0.025, which means p = <0.05. It can be concluded that there is an effect of giving purple sweet potato stew on Increased HB levels in pregnant women. The conclusion in this study is that there is an effect of purple sweet potato stew on increasing HB levels in pregnant women. It is hoped that the results of this study will be used as material for evaluation and policy reference for health workers to apply purple sweet potato decoction to increase Hb in pregnant women to prevent anemia. .